Activation of maternal toll-like receptor-2 causes social deficits and memory impairment in female offspring. Issue 4 (2nd March 2016) - Lee, Younghwa; Jeon, Se Jin; Choi, Ji Woong; Ryu, Jong Hoon
Abstract : To study the relevance of the activation of toll-like receptor-2 and abnormal behavioral properties, we introduced prenatal zymosan, a toll-like receptor-2 ligand, to investigate the effect of maternal immunity on offspring behavior. Only female offspring showed impaired social and cognitive function, suggesting that zymosan may influence females' behavior. Abstract : Supplemental Digital Content is available in the text.